AN APPROACH TO DYNAMIC WEB SERVICE COMPOSITION - Pukhkaiev, Dmytro; Kot, Tetiana; Globa, Larysa (Information and Telecommunication Sciences, 2013)
Today, changeable requirements to modern web-oriented services demand their fast development and constant reengineering. This is realized via dynamic composition of services, allowing to estimate changes of both functional and nonfunctional service parameters. The last ones are considered using Web Services Agreement technique. Nevertheless, state-ofthe- art SLA-aware methods are not able to consider all classes of non-functional parameters. They also don’t provide service run-time support and dynamic reconfiguration. The novel approach to dynamic Web Services Composition, extending SLA with QoS ontology, is described in the paper. It includes service selection agents that use the QoS ontology and WSAgreements, allowing agents to choose the most appropriate service based on quality preferences exposed by service consumer. The proposed approach allows performing dynamic WS composition based on SLA, providing required values of QoS parameters, improving general QoS and decreasing service development and re-engineering time.